Study of different forms of peer violence in primary and secondary schools – a systematic literature review - Primc, Teja (Varstvoslovje, 2021)
Purpose: The purpose of this article is to review the literature on peer violence in primary and secondary schools, and to present key findings of these studies. Design/Methods/Approach: The systematic literature review was performed in the Web of Science and Scopus databases, using the PRISMA method. Findings: A total of 81 articles were selected for the final review. The issue of bullying and cyberbullying is extensive and complex, yet there is still no single definition of this phenomenon. Traditional bullying in primary schools reaches up to 76%, while the prevalence of cyberbullying varies below 10%. The perpetrators are more often boys, while girls are often in the role of victims. Violence is more common in younger children. Risk factors for exposure to violence include belonging to an ethnic minority and the lower economic class. Well-developed emotional intelligence is highlighted as a protective factor. There is more cyberbullying in secondary schools (67%), while traditional bullying is as high as 97%. Male students are more often perpetrators, while female students are more often victims. Students with low self-esteem, members of ethnic minorities and lower economic classes are more exposed to violence. Risk factors for causing violence include a previous history of violence, substance abuse, bad associations, and a poor family environment. Research Limitations/Implications: The findings of the article provide a starting point for the compilation of a comprehensive plan for researching the phenomenon of peer violence in primary and secondary schools in Slovenia, and serve as a basis for the development and implementation of a programme for establishing a safe educational environment. Originality/Value: The article is the starting point for an empirical study that will address peer violence in primary and secondary schools in Slovenia.
Keywords: bullying; cyberbullying; medvrstniško nasilje; osnovne šole; peer violence; primary schools; secondary schools; spletno ustrahovanje; srednje šole; ustrahovanje